PENGARUH PROFITABILITAS, LIKUIDITAS DAN LEVERAGE TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR PERTAMBANGAN BATU BARA YANG TERDAFTAR DI BEI PERIODE 2018 – 2020 - Sahala William Rajagukguk,; Lorina Siregar Sudjiman, (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2022)
This research aimed to determine the effect of Profitability, Liquidity and Leverage on the Firm Value on coal mining sub-sector manufacturing companies listed on the Indonesia Stock Exchange during the period 2018-2020. In this study, the profitability ratio was measured using Return On Equity, Liquidity was measured using The Current Ratio, Leverage was measured using Debt To Equity Ratio, firm value was measured using Price To Book Value. The study used decommissioning and associative methods. The population in this study at coal mining companies listed on the Indonesia Stock Exchange during the 2018-2020 period was 24 companies, with samples obtained using purposive sampling methods of 12 companies. The analysis methods in this study used descriptive statistics, classical assumption tests, multiple linear regressions, hypothesis tests and determination coefficient tests. using the SPSS 26 (Statistical Product and Service Solution) program application. The results of the study obtained by data analysis showed that the independent variables in this study were firm value (PBV) while the independent variables in this study were profitability (ROE), liquidity (CR) and leverage (DER). This study shows partially that profitability has a positive and significant effect on the firm value, liquidity has no positive and insignificant effect on the firm value, leverage has no positive and insignificant effect on the firm value. Simultaneous profitability, liquidity and leverage have an influence on the firm value.